Analisis Kesulitan Belajar Matematika Murid Sekolah Dasar: Karakteristik, Faktor Penyebab, dan Upaya Penanganan - Putri, Helena Anggraeni; Siswanto, Deny Hadi; Wahyuni, Nur; Astiwi, Wuri (Prodi PGMI STAI Sabili Bandung, 2025)
This study was conducted in class V-B of Menggermalang State Elementary School with the aim of identifying the characteristics of students' learning difficulties in mathematics, including the characteristics, causes, and efforts to address them. The research employed a qualitative approach with a case study design. The participants of the study consisted of the principal, the classroom teacher, three V-B students selected based on the teacher's recommendation, and the students' parents. Data were collected through interviews, documentation, and observations. The analysis results showed that: 1) Students' learning difficulties in mathematics were characterized by abnormalities in visual-spatial perception; 2) The factors causing learning difficulties included internal factors such as interest, attitude, motivation, and sensory ability for learning, as well as external factors such as teaching strategies, facilities, family environment, and community; 3) Efforts to address the learning difficulties involved the roles of the teacher and parents, with the teacher providing motivation to the students